The Impact of Discipline, Leadership Style, and Motivation on Productivity : A Case Study at at PT. Balagi, Indonesia - Sutanto, Chrisilla L.; Silitonga, Roland Y. H. (Journal of Management Studies and Development, 2025)
This study analyzes the impact of work discipline, leadership style, and motivation on employee productivity at PT. Balagi, a rattan company in Cirebon focused on exports. Work discipline reflects adherence to work rules, leadership style influences groups to achieve goals, and motivation acts as both internal and external drives to enhance performance. A quantitative approach is used in this research with a Likert-scale-based questionnaire instrument, converted into numerical data for statistical analysis. The results of multiple linear regression analysis show that discipline and motivation significantly affect productivity, while leadership style does not have a significant impact. Simultaneously, the three independent variables contribute 77.5% to employee productivity. This study provides recommendations for further development of research variables, exploration of more specific leadership dimensions, and the use of more complex analysis methods. Practically, it is recommended to improve work discipline and employee motivation through consistent policies, personal development training, and enhancing internal communication within the company.